Risk of cardiovascular mortality with androgen deprivation therapy in prostate cancer: A secondary analysis of the Prostate, Lung, Colorectal, and Ovarian (PLCO) Randomized Controlled Trial. Issue 13 (27th April 2021) - Butler, Santino S.; Mahal, Brandon A.; Moslehi, Javid J.; Nohria, Anju; Dee, Edward C.; Makkar, Rishi; Whitbeck, Amanda; Wangoe, Janet; Mouw, Kent W.; Nguyen, Paul L.; Muralidhar, Vinayak
Abstract : BACKGROUND: For men with radiation‐managed prostate cancer, there is conflicting evidence regarding the association between androgen deprivation therapy (ADT) and cardiovascular mortality (CVM), particularly among those who have with preexisting comorbidities. The objective of this study was to analyze the association between ADT and CVM across patient comorbidity status using prospectively collected data from a large clinical trial. METHODS: In total, 1463 men were identified who were diagnosed with clinically localized, intermediate‐risk/high‐risk prostate cancer (T2b‐T4, Gleason 7‐10, or prostate‐specific antigen >10 ng/mL) from 1993 to 2001 and managed with either radiation therapy (RT) alone or RT plus ADT during the randomized Prostate, Lung, Colon, and Ovarian (PLCO) Cancer Screening Trial. Adjusted hazard ratios (aHRs) for cause‐specific mortality (prostate cancer‐specific mortality vs other‐cause mortality—including the primary end point of CVM [death from ischemic heart disease, cerebrovascular accident, or other circulatory disease]) were determined using Fine and Gray competing‐risk regression analysis and stratified by comorbidity history. RESULTS: There was no difference in the risk of 5‐year CVM between ADT plus RT and RT alone (2.3% vs 3.3%, respectively; aHR, 0.69; 95% CI, 0.38‐1.24; P = .21) overall or on subgroup analysis among men with a history of ≥1 preexisting comorbidities (3.2% vs 5.3%, respectively; aHR, 0.83; 95% CI, 0.43‐1.60; P = .58), ≥2 preexisting comorbidities (6.9% vs 8.3%, respectively; aHR, 0.95; 95% CI, 0.40‐2.25; P = .90), or cardiovascular disease/risk factors (3.6% vs 4.3%, respectively; aHR, 0.85; 95% CI, 0.44‐1.65; P = .63). These results were all similar when each component of CVM was analyzed separately—either cardiac, stroke, or other vascular mortality ( P > .05). CONCLUSIONS: This study provides prospectively collected evidence that the use of ADT plus RT, compared with RT alone, is not associated with an increased risk of CVM, even among subgroups of men who have preexisting comorbidities and cardiovascular disease. Abstract : In this secondary analysis of a prospective trial of 1463 men with radiation‐treated, localized, intermediate‐risk/high‐risk prostate cancer, 5‐year cardiovascular mortality is comparable between androgen deprivation therapy plus radiation therapy and radiation therapy alone (overall, 2.3% vs 3.3%, respectively), even among those who have preexisting comorbidities or cardiovascular disease.